Ingestion of Unknown Snake Venom: A Case Report - Utkarsh Gaur; Charuta Gadkari; Aditya Pundkar (Journal of Clinical and Diagnostic Research, 2024)
Venom from a snake is extremely uncommonly consumed by humans. It can be administered in a variety of ways, including a direct bite on the tongue or other parts of the body, or it can be taken as a venom pill at rave parties. The belief is that upon consumption, it provides virility, a sense of elation, and excitement, among other effects. However, it is more often dangerous to the human body and can even be fatal. Only a very small number of cases have been described in publications. In the present case report, a 36-year-old male patient who was an alcoholic and had a history of psychiatric disease initially arrived with anxiety as a result of having consumed snake venom the day before. As for the patient’s vital signs, they were acceptable. For observation, the patient was admitted to the intensive care unit reserved for medicine. However, antisnake venom was not administered. After 24 hours, he was released from the hospital. This is an unusual case where the patient was relatively unharmed after the consumption and didn’t show any obvious lasting effects on the neurological or haematological systems. If the venom is not effectively broken down in the intestines and is absorbed as such, drinking snake venom can have deadly repercussions. The treatment is determined by the features that the patient presents. In the present case, antivenom was not administered, as the need was not justified. However, there may arise situations in other cases where it should be administered sparingly.